Radicalism in Indonesia: Modelling and Legal Construction - Usman, Usman; Hafrida, Hafrida; Rapik, Mohamad; Maryati, Maryati; Sabri, Ahmad Zaharuddin Sani Ahmad (Journal of Indonesian Legal Studies, 2023)
Radicalism, commonly intertwined with terrorism, assumes a critical role in Indonesia's efforts to counter and deradicalize individuals as part of its broader counterterrorism strategies. Despite the incorporation of contra-radicalization and deradicalization measures within the Indonesian Anti-Terrorism Law, the legal framework lacks a precise definition of radicalism. The absence of a clear legal concept prompts ongoing debates among academics and political entities, leaving the definitive elucidation of radicalism largely within the purview of the government. This article contends that for the sake of achieving conceptual uniformity and ensuring legal clarity, a formal regulation addressing the nuanced dimensions of radicalism is imperative. The objective herein is to scrutinize the existing model for gauging radicalism in the Indonesian context and subsequently formulate a robust legal construct surrounding this complex phenomenon. To this end, a set of four criteria—intolerance, fanaticism, exclusiveness, and revolutionary fervor—has been devised to quantitatively measure the extent of radicalism. This measurement process involves the administration of interviews or surveys, with the resultant data shedding light on respondents' inclinations and tendencies. The proposed legal framework posits that an individual or group can be categorized as radical only when they meet the predefined criteria encapsulated within the regulations, encompassing the four specified dimensions. By delineating and operationalizing these criteria, this research endeavors to contribute to the development of a comprehensive legal framework for addressing radicalism in Indonesia. This approach not only facilitates a more nuanced understanding of radicalism but also provides a tangible basis for legal categorization and intervention. Ultimately, the aim is to enhance the effectiveness of counterterrorism efforts by establishing a clear and standardized definition of radicalism within the Indonesian legal landscape.